Dual function of the NDR-kinase Dbf2 in the regulation of the F-BAR protein Hof1 during cytokinesis - Meitinger, Franz; Pereira, Gislene (Molecular biology of the cell, 2013)
The conserved NDR-kinase Dbf2 plays a critical role in cytokinesis in budding yeast. Among its cytokinesis-related substrates is the F-BAR protein Hof1. Hof1 colocalizes at the cell division site with the septin complex and, as mitotic exit progresses, moves to the actomyosin ring (AMR). Neither the function of Hof1 at the septin complex nor the mechanism by which Hof1 supports AMR constriction is understood. Here we establish that Dbf2 has a dual function in Hof1 regulation. First, we show that the coiled-coil region, which is adjacent to the conserved F-BAR domain, is required for the binding of Hof1 to septins. The Dbf2-dependent phosphorylation of Hof1 at a single serine residue (serine 313) in this region diminishes the recruitment of Hof1 to septins both in vitro and in vivo. Genetic and functional analysis indicates that the binding of Hof1 to septins is important for septin rearrangement and integrity during cytokinesis. Furthermore, Dbf2 phosphorylation of Hof1 at serines 533 and 563 promotes AMR constriction most likely by inhibiting the SH3-domain-dependent interactions of Hof1. Thus our data show that Dbf2 coordinates septin and AMR functions during cytokinesis through the regulation/control of Hof1.